Leveraging Data for University Activities: A Case Study of MNUE - Chinbat, Dolgorjav (Lavai - International Journal of Education, 2023)
This article shows the critical role of data utilization within the daily activities of organizations, focusing on its significance in the context of a university setting. Data, continuously accumulated over a long period, serves as an indelible record of all ongoing activities involving stakeholders of any organization. Importantly, this process-generated data stands as a priceless organizational asset, showing us the reality of operational dynamics. It is imperative to utilize this data's potential promptly, as its value diminishes over time. As a center for education and research, universities produce some fundamental products and services, simultaneously generating various types of data in its frame. This includes: i) The development and delivery of competitive, high-quality programs to meet the demands of students and other stakeholders ii) Equipping the workforce with advanced knowledge and skills acquired through these programs, thereby enhancing their readiness for the labor market. iii) Active contribution to societal advancement through the generation of diverse research results. Data-driven decision-making varies across different levels of the university system. This article conducts a comparative analysis, elucidating exemplary practices in data utilization from other universities and contrasting them with the data usage landscape at the Mongolian National University of Education. The study draws upon a review of 12 research works authored by international scholars, offering insights into the data utilization experiences. Furthermore, the research assesses the current state of data utilization within MNUE by examining three official documents and analyzing five locally conducted research works. The findings underscore the immediate need for specific action items to harness the full potential of data within MNUE's daily activities. We also highlight the imperative transition from data accumulation to actionable insights, fostering positive change within the university landscape. This research article elucidates the pivotal role of data in enhancing operational efficiency, facilitating informed decision-making, and ultimately fortifying the overall effectiveness of educational institutions. Их сургуулийн үйл ажиллагаанд өгөгдлийн гүйцэтгэх үүрэг:МУБИС-ийн жишээн дээр Энэхүү судалгааны ажлаар байгууллагын өдөр тутмын үйл ажиллагаанд өгөгдөл ашиглалтын чухал үүргийг харуулж, их сургуулийн орчинд түүний ач холбогдлыг авч үзлээ. Байгууллагын өдөр тутмын үйл ажиллагааны өгөгдөл (дата) нь удаан хугацаанд тасралтгүй цуглардаг, оролцогч талуудын байнгын үйл ажиллагааны ул мөр байдаг. Хамгийн чухал нь энэхүү процессын дата нь тухайн орчинд өрнөж буй үйл явцын мөч бүрээс органик байдлаар үүсдэг, процессын урсгалын үнэн дүр төрх учраас байгууллагын үнэ цэнтэй хөрөнгө юм. Гагцхүү цаг хугацааны хувьд үнэ цэнээ алдахаас өмнө үүнийг эргэлтэд оруулж, үр ашгийг нь хүртэх нь чухал. Их сургууль нь сургалт эрдэм шинжилгээний байгууллага болохын хувьд i) өрсөлдөхүйц чанартай хөтөлбөрийг боловсруулж, худалдан авагчдад санал болгох, ii) тэр хөтөлбөрөөр суралцсан өндөр мэдлэг, ур чадвартай боловсон хүчнийг хөдөлмөрийн зах зээлд нийлүүлэх болон iii) төрөл бүрийн судалгааны үр дүнгээр нийгэмд хувь нэмрээ оруулах гэсэн үндсэн бүтээгдэхүүн, үйлчилгээ үйлдвэрлэж, энэ хүрээндээ төрөл бүрийн дата үүсгэж байдаг. Өгөгдөлд үндэслэн шийдвэр гаргах нь системийн түвшин бүрд ялгаатай байх учир бусад их сургуулиуд дээрх процессын өгөгдлөө хэрхэн ашиглаж байгаа сайн жишээ болон Монгол улсын боловсролын их сургуулийн хувьд өгөгдлийн хэрэглээ ямар түвшинд байгааг энэ өгүүллээр харьцуулж үзлээ. Бид гадаадын судлаачдын 12 бүтээл сонгож, өгөгдлийн хэрэглээний туршлага ямар хүрээнд байгааг шинжиллээ. МУБИС-ийн өнөөгийн байдалтай харьцуулахын тулд тус сургуулийн албан баримт 3, мөн дотоодын 5 бүтээлийг судалсан. Тус сургуулийн хувьд өгөгдлийг хуримтлуулахаас илүүтэй бодитоор хэрэглэх ойлголт руу шилжих зайлшгүй шаардлага байна, өнөөг хүртэл хуримтлагдсан өгөгдлийг ашиглан нэн даруй хийвэл зохих хэд хэдэн ажил байна гэж дүгнэлээ. Энэхүү өгүүлэл нь үйл ажиллагааны үр ашгийг дээшлүүлэх, мэдээлэлтэй шийдвэр гаргахад дөхөм үзүүлэх, эцсийн дүндээ боловсролын байгууллагуудын ерөнхий үр нөлөөг бэхжүүлэхэд өгөгдлийн гол үүргийг тодруулсан болно. Түлхүүр үг: Өгөгдөл, үйл ажиллагааны өгөгдөл, өгөгдлийн шинжилгээ, их сургуулийн өгөгдөл